2016
DOI: 10.1016/j.jth.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in walking, body mass index, and cardiometabolic risk factors following residential relocation: Longitudinal results from the CARDIA study

Abstract: Background While many studies have found the built environment to be associated with walking, most have used cross-sectional research designs and few have examined more distal cardiometabolic outcomes. This study contributes longitudinal evidence based on changes in walking, body mass index (BMI), and cardiometabolic risk following residential relocation. Methods We examined 1,079 participants in the CARDIA study who moved residential locations between 2000 and 2006 (ages 32–46 in 2000, 49% white/51% black, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 57 publications
4
67
1
1
Order By: Relevance
“…Alternatively, if the authors explicitly discussed that one model is less biased than the other, we then coded this association based on the less biased model. For example, Braun et al tested the association between a walkability index and walking outcomes using both random and fixed effects models 27. They argued that estimates from random effects models were more biased because of residual self-selection bias; we therefore coded this association based on results from the fixed effects model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, if the authors explicitly discussed that one model is less biased than the other, we then coded this association based on the less biased model. For example, Braun et al tested the association between a walkability index and walking outcomes using both random and fixed effects models 27. They argued that estimates from random effects models were more biased because of residual self-selection bias; we therefore coded this association based on results from the fixed effects model.…”
Section: Methodsmentioning
confidence: 99%
“…Neither do they have control over the dose of the intervention. As environmental change is usually slow and incremental,27 it may not provide a sufficient ‘dose’ required for behavioural change during the time frame of the evaluation. In fact, some evaluations of environmental interventions on physical activity had mixed findings14 possibly due to these challenges.…”
Section: Introductionmentioning
confidence: 99%
“… 3.2 Antihypertensive medications: The effect of one standard dose of antihypertensive medications is estimated between 5.7 mmHg to 11.7 mmHg and 3.1 mmHg to 6.9 mmHg in reduced systolic and diastolic blood pressure, depending upon pre-treatment level ( Law et al, 2009 ). Increasing neighbourhood walkability: A cohort study showed 1-standard deviation (7.95 unit) increase in neighbourhood walkability was associated with a 0.81 mmHg reduction (95%CI -1.55 to -0.07) in systolic blood pressure ( Braun et al, 2016 ). Increasing neighbourhood walkability could reduce systolic blood pressure by a little under 1 mmHg, compared with a 5.7–11.7 mmHg reduction from a standard dose of antihypertensive medication (depending upon pre-treatment levels).…”
Section: Resultsmentioning
confidence: 99%
“… Chiu et al, 2016 ), with the effect partially mediated by change in body weight ( Chaix et al, 2008 ). A recent US-based cohort study ( Braun et al, 2016 ) tracked change in blood pressure over 6 years among people moving from neighbourhoods of low to high walkability. ‘Fixed effect’ models adjusted for time-varying sources of confounding found a 1-standard deviation increase in local walkability to be associated with a 0.81 mmHg reduction (95%CI -1.55 to -0.07) in systolic blood pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation